Stunting Prevention Activities Through Cooking Demonstration Method Of Making Moringa Leaf Pudding - Asrul, Nur Al Marwah (PABBURA : Health Service Journal, 2024)
Despite a decline in prevalence, stunting remains a significant health issue in the Pangkajene dan Kepulauan District, warranting ongoing attention and intervention. Satando Island and Saugi Island, both part of the Regional Marine Conservation Area of Pangkep Regency, continue to report cases of children with height measurements below the standard for their age. Observations and interviews indicate the presence of abundant Moringa trees on both islands. In response to this, community service initiatives were implemented, specifically focusing on a demonstration of Moringa leaf pudding preparation. The project, titled "Preventing Stunting through the Moringa Leaf Pudding Cooking Demonstration Method," successfully enhanced the skills of local health cadres. This improvement was evidenced by the evaluation, which included photographic documentation showing the cadres’ ability to prepare and serve Moringa leaf pudding effectively. Keywords: Moringa Leaf Pudding, Island, Stunting